Simulation Method Linking Dense Microalgal Culture Spectral Properties in the 400–750 nm Range to the Physiology of the Cells. Issue 6 (June 2016) - Bellini, Sarah; Bendoula, Ryad; Le Floc'h, Emilie; Carré, Claire; Mas, Sébastien; Vidussi, Francesca; Fouilland, Eric; Roger, Jean-Michel
This work describes a method to model the optical properties over the (400−750 nm) spectral range of a dense microalgal culture using the chemical and physical properties of the algal cells. The method was based on a specific program called AlgaSim coupled with the adding–doubling method: at the individual cell scale, AlgaSim simulates the spectral properties of one model, three-layer spherical algal cell from its size and chemical composition. As a second step, the adding–doubling method makes it possible to retrieve the total transmittance of the algal medium from the optical properties of the individual algal cells. The method was tested by comparing the simulated total transmittance spectra for dense marine microalgal cultures of Isochrysis galbana (small flagellates) and Phaeodactylum tricornutum (diatoms) to spectra measured using an experimental spectrophotometric setup. Our study revealed that the total transmittance spectra simulated for the quasi-spherical cells of Isochrysis galbana were in good agreement with the measured spectra over the whole spectral range. For Phaeodactylum tricornutum, large differences between simulated and measured spectra were observed over the blue part of the transmittance spectra, probably due to non-spherical shape of the algal cells. Prediction of the algal cell density, mean size and pigment composition from the total transmittance spectra measured on algal samples was also investigated using the reversal of the method. Mean cell size was successfully predicted for both species. The cell density was also successfully predicted for spherical Isochrysis galbana, with a relative error below 7%, but not for elongated Phaeodactylum tricornutum with a relative error up to 26%. The pigments total quantity and composition, the carotenoids:chlorophyll ratio in particular, were also successfully predicted for Isochrysis galbana with a relative error below 8%. However, the pigment predictions and measurements for Phaeodactylum tricornutum showed large discrepancies, with a relative error up to 88%. These results give strong support for the development of a promising tool providing rapid and accurate estimations of biomass and physiological status of a dense microalgal culture based on only light transmittance properties.